Association of congenital heart diseases with extracardiac anomalies - Dewangan, Mithlesh (International Journal of Contemporary Pediatrics, 2017)
Background: Congenital heart diseases are one of the main causes of death among the congenital malformations. An extracardiac malformation further increases the risk of morbidity and mortality to these patients, in addition to risks of surgical correction. So here comes the importance of extracardiac malformation. Methods:This prospective observational study was conducted at Neonatology Section, Department of Pediatrics, Jawaharlal Nehru Medical College, Aligarh Muslim University, Aligarh. The study was conducted over a period of 2 years (from January 2015 to December 2016). Newborns with congenital heart disease were examined for extracardiac defects. Results: This hospital based cross-sectional study found that there were 121 cases of congenital heart diseases among 11030 live births making an incidence of 1.09% Out of these 73.5% were acyanotic heart diseases and 26.5% were cyanotic heart disease. Extracardiac anomalies were found in 38 (31.5%) cases. Conclusions:Association of Congenital heart disease with extracardiac anomalies is well known. Syndromes are most commonly associated.